Giving offspring a head start in life: field and experimental evidence for selection on maternal basking behaviour in lizards. - Wapstra, E; Uller, T; While, G; Olsson, M; Shine, R (2010)
The timing of birth is often correlated with offspring fitness in animals, but experimental studies that disentangle direct effects of parturition date and indirect effects mediated via variation in female traits are rare. In viviparous ectotherms, parturition date is largely driven by female thermal conditions, particularly maternal basking strategies. Our field and laboratory studies of a viviparous lizard (Niveoscincus ocellatus) show that earlier-born offspring are more likely to survive through their first winter and are larger following that winter, than are later-born conspecifics. Thus, the association between parturition date and offspring fitness is causal, rather than reflecting an underlying correlation between parturition date and maternal attributes. Survival selection on offspring confers a significant advantage for increased maternal basking in this species, mediated through fitness advantages of earlier parturition. We discuss the roles of environmentally imposed constraints and parent-offspring conflict in the evolution of maternal effects on parturition date.